Influence in the reproductive planning and the women's satisfaction with the discovery of being pregnant in the quality of prenatal care in Brazil - José Marcos de Jesus Santos; Thais Santos de Matos; Rosemar Barbosa Mendes; Carla Kalline Alves Cartaxo Freitas; Adriana Moraes Leite; Iellen Dantas Campos Verdes Rodrigues
Abstract Objectives: to analyze the influence on reproductive planning and the women's satisfaction with the discovery of being pregnant in prenatal care characteristics. Methods: a cross-sectional and quantitative study was carried out between March and July 2018 at a low-risk maternity hospital in the Brazilian Northeast region. A total of 652 puerperal women were evaluated in an interview and by their prenatal care card. The Chi-square test and the Odds Ratio were used for statistical analysis. Results: the pregnancy planning was reported by 42% (n=274), and the women's satisfaction of being pregnant was 64.1% (n=418) of the interviewees. Reproductive planning was associated with early initiation of prenatal care (OR=2.48, CI95%=1.61-3.82) and the women received information about the referral maternity for childbirth (OR=1.44, CI95%=1.05-1.99). The women's satisfaction with their pregnancy was also associated with early initiation of prenatal care (OR=2.18; CI95%=1.47-3.25). It should be noted that the performance of six or more prenatal care consultations was less frequent among pregnant women who had not planned their pregnancy (OR=0.43, CI95%=0.27-0.66) and they felt unsatisfied with the discovery of being pregnant (OR=0.56; CI95%=0.37-0.84). Conclusions: Pregnancy planning and women's satisfaction with the discovery of being pregnant favors the performance of prenatal care with better indicators.